2020
DOI: 10.1177/2292550320928560
|View full text |Cite
|
Sign up to set email alerts
|

The Materials Utilized in Cranial Reconstruction: Past, Current, and Future

Abstract: Background: Cranioplasty (CP) is associated with high complication rates compared to other common neurosurgical procedures. Several graft materials are used for CP, which may contribute to the high complication rates, but data in the literature regarding the influence of graft material on post-CP outcomes are inconsistent making it difficult to determine if, when, and to what extent the graft material impacts the rate of perioperative complications. There is an increased demand to identify and develop superior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 68 publications
(261 reference statements)
0
10
0
Order By: Relevance
“…The implant was subsequently removed, yet the patient’s hospital course was complicated by postoperative seizures; this has similarly been cited in the literature 5 . Moreover, the literature suggests a slightly higher complication and infection rate associated with PEEK compared with autologous materials 6–9 . In a review of 280 patients who underwent cranioplasty with autologous bone, Schuss and colleagues, reported a complication rate of 16.4%, whereas Chang and colleagues, reported that allografts had higher rates of infection than autologous bone grafts 5,10,11 .…”
Section: Discussionmentioning
confidence: 82%
“…The implant was subsequently removed, yet the patient’s hospital course was complicated by postoperative seizures; this has similarly been cited in the literature 5 . Moreover, the literature suggests a slightly higher complication and infection rate associated with PEEK compared with autologous materials 6–9 . In a review of 280 patients who underwent cranioplasty with autologous bone, Schuss and colleagues, reported a complication rate of 16.4%, whereas Chang and colleagues, reported that allografts had higher rates of infection than autologous bone grafts 5,10,11 .…”
Section: Discussionmentioning
confidence: 82%
“…Such materials quickly become commercially unviable and therefore unlikely to remain in clinical practice over extended periods of time. Moreover, no single craniomaxillofacial implant material has emerged with the ideal biomimetic properties [ [24] , [25] , [26] ], and, as such, the choice of implant material should be tailored to optimise each clinical case based on an assessment of the material properties ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Typically, cranioplasty is performed after a craniotomy, and the development of the defect and its correction is separated by time. 1 It focuses on using surgical procedures to treat skull injuries and defects. Craniotomy is a surgical treatment that involves removing a portion of the skull to relieve pressure on the brain caused by swelling or bleeding.…”
Section: Introductionmentioning
confidence: 99%